2014
DOI: 10.4238/2014.september.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of CCoAOMT in interspecific hybrid of Acacia auriculiformis x Acacia mangium - a key gene in lignin biosynthesis

Abstract: ABSTRACT. This study was directed at the understanding of the function of CCoAOMT isolated from Acacia auriculiformis x Acacia mangium. Full length cDNA of the Acacia hybrid CCoAOMT (AhCCoAOMT) was 1024-bp long, containing 750-bp coding regions, with one major open reading frame of 249 amino acids. On the other hand, full length genomic sequence of the CCoAOMT (AhgflCCoAOMT) was 2548 bp long, containing three introns and four exons with a 5' untranslated region (5'UTR) of 391 bp in length. The 5'UTR of the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…High levels of CCOMT expression is associated with xylem development in woody plants (Shi et al, 2010;Yang et al, 2014). At present, many studies have used genetic engineering to suppress CCOMT expression to downregulate lignin (Wagner et al, 2011;Li et al, 2013;Pang et al, 2014;Zhang et al, 2014). In the present study, two CCOMT genes (PbCCOMT1 and PbCCOMT3) involved in lignin biosynthesis have been identified.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…High levels of CCOMT expression is associated with xylem development in woody plants (Shi et al, 2010;Yang et al, 2014). At present, many studies have used genetic engineering to suppress CCOMT expression to downregulate lignin (Wagner et al, 2011;Li et al, 2013;Pang et al, 2014;Zhang et al, 2014). In the present study, two CCOMT genes (PbCCOMT1 and PbCCOMT3) involved in lignin biosynthesis have been identified.…”
Section: Discussionmentioning
confidence: 85%
“…Suppression of CCOMT expression in maize showed that the lignin content was decreased and the ratio of S/G lignin units was increased . Research showed that heterologously expressed anti-AcCCOMT increased the levels of S units, G units, and total lignin in tobacco (Pang et al, 2014). The results of previous studies have shown that PbCCOMT genes are expressed at high levels during the early stages of fruit development, which might promote the accumulation of pear stone cells (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Different approaches used to downregulate CCoAOMT, including antisense RNA, RNA interference, or gene knockout, resulted in decreased lignin content in plants, which was associated with collapsed vascular bundles, lower height, lower biomass and developmental retardation (Do et al 2007 ). Plants with downregulated CCoAOMT genes also exhibit modified lignin subunit composition due to disturbances in syringyl and guaiacyl monolignol synthesis (Li et al 2013 ; Meyermans et al 2000 ; Pang et al 2014 ; Pinçon et al 2001 ; Toraman et al 2016 ; Zhong et al 1998 ). CCoAOMT overexpression produces the opposite effects, including increased lignin content, plant height and silique length (Zhang et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin in stem cell walls of PAL -knockdown plants in Brachypodium distachyon is reduced by approximately 43% 33 . Downregulation of C4H in hybrid eucalyptus ( Eucalyptus urophylla × Eucalyptus grandis ) 34 , 4CL in hybrid poplar ( Populus tremula × Populus alba ) 35 , CCR in birch ( Betula platyphylla × Betula pendula ) 36 , CAD in Arabidopsis thaliana 37 , and a CCoAOMT homolog in tobacco ( Nicotiana tabacum ) 38 leads to varying degrees of reduction in lignin content compared to controls. The suppression of these genes also affects plant development, especially the repression of CCR , which reduces the thickness of secondary walls.…”
Section: Discussionmentioning
confidence: 99%